2005
DOI: 10.1002/eqe.510
|View full text |Cite
|
Sign up to set email alerts
|

An efficient three-dimensional solid finite element dynamic analysis of reinforced concrete structures

Abstract: SUMMARYMost of the ÿnite element analyses of reinforced concrete structures are restricted to two-dimensional elements. Three-dimensional solid elements have rarely been used although nearly all reinforced concrete structures are under a triaxial stress state. In this work, a three-dimensional solid element based on a smeared ÿxed crack model that has been used in the past mainly for monotonic static loading analysis is extended to cater for dynamic analysis. The only material parameter that needs to be input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
(27 reference statements)
0
29
0
Order By: Relevance
“…13 of 17 Figure 8 shows the dynamic response [60] of the 5-5-■ and 5-6-■ buildings with a range of materials properties used for the constituent parts. Concrete characteristic resistances of fck = 300 kg/cm 2 (H-30) and fck = 350 kg/cm 2 (H-35), and steel elastic limits of fyk = 4000 kg/cm 2 (B 400-S) and fyk = 6000 kg/cm 2 (B 600-S) were used for this set of analyses.…”
Section: Dynamic Analysismentioning
confidence: 99%
“…13 of 17 Figure 8 shows the dynamic response [60] of the 5-5-■ and 5-6-■ buildings with a range of materials properties used for the constituent parts. Concrete characteristic resistances of fck = 300 kg/cm 2 (H-30) and fck = 350 kg/cm 2 (H-35), and steel elastic limits of fyk = 4000 kg/cm 2 (B 400-S) and fyk = 6000 kg/cm 2 (B 600-S) were used for this set of analyses.…”
Section: Dynamic Analysismentioning
confidence: 99%
“…Modeling of reinforced concrete (RC) structures with the use of 3D detailed models is usually performed by research teams [1][2][3][4][5] or by large consultancy companies [6][7] that foresee the thorough investigation of the mechanical behavior of geometrically complicated RC structures. Researchers have been using this modeling type so as to verify experimental results or develop new constitutive models in an attempt to derive a numerically objective modeling method that will eventually provide the ability of performing assessment analysis for any type of RC structure geometry and design.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have been published on plasticity models, smeared crack approach or combination of these models, specifically implemented on concrete structures (Rashid [123] (1968), Červenka and Gerstle [124] (1971), Owen et al [125] (1983), Bažant and Oh [126] (1983), De Borst [127] (1986), Simo and Ju [128] (1987), Rots [129] (1989), Pramono and Willam [130] (1989), Kotsovos and Pavlovic [8] (1995), Etse [131] (1992), Feenstra [132] (1993), Feenstra et al [133] (1998), Menetrey et al [134] (1997), Bažant et al [135] (2000), Bažant and Caner [136,137] (2005), Spiliopoulos and Lykidis [138] (2006), Sato and Naganuma [139] (2007), Červenka et al [140] (2008)), but a few researchers stated that their algorithms showed computational accuracy and numerical robustness. Furthermore, concerning the combination of plasticity with smeared crack models, none of them succeeded in providing a computationally efficient code even when dealing with relatively small-scale FE models.…”
Section: Page 95 Of 272mentioning
confidence: 99%
“…concrete material model combined with the smeared crack approach), the sensitivity of such models to various user-defined parameters, becomes more pronounced [140] . These difficulties led a number of researchers [6,8,138,199,200,205] to use higher order elements (20-noded and 27-noded hexahedral elements) in connection with high integration rules (3x3x3). The use of this type of 3D elements and numerically unstable material models has a direct consequence on the efficiency of the numerical simulations, requiring many NR iterations per load step and thus considerable computational effort, even for small-scale FE models.…”
Section: Brief Overviewmentioning
confidence: 99%
See 1 more Smart Citation